Strategic Transfer Pricing - Alles, Michael; Datar, Srikant (Management Science, 1998)
Most research into cost systems has focused on their motivational implications. This paper takes a different approach, by developing a model where two oligopolistic firms strategically select their cost-based transfer prices. Duopoly models frequently assume that firms game on their choice of prices. Product prices, however, are ultimately based on the firms' transfer prices that communicate manufacturing costs to marketing departments. It is for this reason that transfer prices will have a strategic component to them. We derive implications for cost system choice and transfer pricing, including showing that firms may cross subsidize their products—a result consistent with the empirical evidence.